2008
DOI: 10.1677/erc-07-0081
|View full text |Cite
|
Sign up to set email alerts
|

Expression of progesterone and estradiol receptors in normal adrenal cortex, adrenocortical tumors, and primary pigmented nodular adrenocortical disease

Abstract: Adrenal tumors occur more frequently in women and are the leading cause of Cushing's syndrome during pregnancy. We aimed to evaluate the potential role of sex steroids in the susceptibility of women to adrenocortical tumors. We evaluated the presence of the progesterone receptor (PR), estradiol receptors (ERs), and aromatase in 5 patients with primary pigmented nodular adrenal disease (PPNAD), 15 adrenocortical adenomas (ACAs) and adjacent normal tissues, 12 adrenocortical carcinomas (ACCs), and 3 normal adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 40 publications
2
45
0
1
Order By: Relevance
“…In adrenal cortex of different species both receptors have been identified, however, the relative expression of both receptor types differs significantly. Contrary to human adrenal cortex, in the rat adrenal cortex ERa mRNA is far more abundant than the ERb [29][30][31][32]. Likewise, in chicken adrenals the relative expression of ERa mRNA was higher than ERb mRNA [33].…”
Section: Discussionmentioning
confidence: 78%
“…In adrenal cortex of different species both receptors have been identified, however, the relative expression of both receptor types differs significantly. Contrary to human adrenal cortex, in the rat adrenal cortex ERa mRNA is far more abundant than the ERb [29][30][31][32]. Likewise, in chicken adrenals the relative expression of ERa mRNA was higher than ERb mRNA [33].…”
Section: Discussionmentioning
confidence: 78%
“…In humans, the ratio of the two isoforms is critical for regulating biological responses of PgR in target tissues [26]. The two PgR isoforms are present in normal adrenal tissue and in ACC and have a similar expression rate [27], whereas NCI-H295R cells display a higher expression of PgRB than PgRA [27]. We found that PgRB is predominantly expressed in NCI-H295R cells and that the PgR antagonist mifepristone was able to antagonize AA-induced NCI-H295R cell toxicity in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of particular hormone receptors could impact on tumour growth and cortisol secretion, which might provide an opportunity for targeted therapy. Increased expression of growth hormone receptor (GHR) and progesterone receptor (PR) has been observed in human cortisol-secreting ATs (Lin et al, 1997;de Cremoux et al, 2008), which might represent an autocrine PR-GHR mechanism, similar to that seen in canine mammary carcinomas (Mol et al, 1995). Overexpression of somatostatin receptors (SSTR1-5) (Mariniello et al, 2011) and the presence of D2-like dopamine receptors (DRD2 and DRD4) have also been reported in human ATs (Pivonello et al, 2004).…”
mentioning
confidence: 85%